The Karen villagers knowledge development in road construction: a case study of Panoki Kopadoh (PNK) route - Uba Sirikaew; Songklod Sae-Ueng; Somkiat Khwanpruk; Thanom Sriworasa (My University, 2018)
The Karen, of Panoki village agreed to upgrade the unpaved PNK route to a bamboo reinforced concrete road which used money from the donation. At the beginning of the road construction project, 2010, there were many problems concerned with construction technique and accidents. Civil Engineering Department, Engineering Faculty, King Mongkut’s Institute of Technology Ladkrabang (KMITL) was invited to be a road construction consultant of Panoki-Kopadoh (PNK) route during 2012 to 2017. As the villages of Panoki in Tak province and Kopadoh in Chiang Mai province are in Thailand’s northern remote mountainous areas connected by a 16.5 km unpaved narrow track of Panoki-Kopadoh (PNK) route. In fact, the majority of volunteer villagers understand only the Karen language, lack the basic construction skills, and show no regard for personal safety and hygiene. The consulting team thus provided a training program prior to construction and assisted with technical advice since the onset of the project. As an achievement of the project depends on people participation, this research is to examine the pre-and post-training local workers’ knowledge development and attitudes toward the academic services provided by KMITL through direct observations, a Likert-scale-based questionnaire, and in-depth interviews. The findings reveal that the participating villagers have learned to construct a bamboo reinforced concrete road and are intent on applying the knowledge to similar projects in the future. They exhibit the higher level of knowledge development following the training and also hold a positive attitude toward KMITL’s academic services.
Keywords: Road Construction; Southeast Asian Sociopolitical Studies